The impact of the Russia-Ukraine conflict on the energy expenditure of public Italian healthcare organizations – A nationwide interrupted series analysis - Guidotti, Elisa; Di Marco, Marco (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Healthcare organizations are complex systems characterized as highly energy intensive structures. Italian healthcare organizations are under increasing pressure due to the external energy dependency, especially following the Russia-Ukrainian conflict. Indeed, the ongoing war has generated low energy availability and outbreaking energy costs, thus leading to the aim of the study that is to measure the effect of the Russia-Ukraine war on the energy expenditure of public Italian healthcare organizations.Study design & methods. An Interrupted Times Series analysis was conducted across the period 2017-2022. Details were provided for the nineteen regions and two autonomous provinces. The outcome used was the energy expenditure amount across public healthcare organizations, a Poisson regression model was used. The revenues of public healthcare organizations were included as an offset variable to convert the outcome into a rate and adjust for any potential changes in revenues over time.Results. The model suggested that there is strong evidence of a rise in the energy expenditure following the conflict, with an increase of 56% [relative risk (RR) 1.75] in Italy. All the Italian regions registered a notable increase of the energy expenditure in public healthcare organizations after the conflict, despite inter-regional variability was observed.Conclusions. Several interventions have been carried out to support enterprises and healthcare organizations in managing energy expenditure increases, though National strategies and investments should be set up to guarantee public healthcare organizations’ sustainability in the long run.